Aortic arch interruption presenting with absence of all limb pulses. Issue 1 (January 1979) - Sharratt, G P; Leanage, R; Monro, J L; Shinebourne, E A
Abstract : Three patients with aortic arch anomalies presented with severe heart failure, acidaemia, and poor or absent upper and lower limb pulses. Prominent carotid arterial pulsations were detected which distinguished the condition clinically from aortic atresia. In 2 patients with a left aortic arch, interruption was distal to the left common carotid artery and there was an aberrant right subclavian. In the 3rd patient with a right aortic arch, interruption was distal to the right common carotid and there was an aberrant left subclavian artery. By dilating the narrowed ductus, prostaglandin E2 infusion corrected the acidosis. Successful surgical correction was achieved in one patient by direct anastomosis of descending aorta to ascending aorta and the base of the left common carotid artery.